Regioselective Biomimetic Synthesis of Dimeric Oxyresveratrol Derivatives - Ran, Lu; Li, Hongpeng; Chao, Ge; Kang, Xiaodong; Lei, Tian; Li, Wenling (Synlett, 2020)
Oxyresveratrol and its methylated derivative as coupling precursors were efficiently prepared in four steps, with Wittig reactions and subsequent isomerization reactions as the key steps. The coupling reactions of oxyresveratrol under various oxidative conditions gave a complex and inseparable mixture of coupling products. The oxidative dimerizations of methylated oxyresveratrols catalyzed by horseradish peroxidase–H2O2 or FeCl3·6H2O in an acetone system predominantly produced the 8–5-coupled and 8–10-coupled dihydrobenzofuran-type dimers, respectively. This regioselective biomimetic strategy might be useful in synthesizing other dimeric oxyresveratrol derivatives.
Keywords: oxyresveratrol; biomimetic synthesis; oligostilbenes; oxidative coupling; dimerization; regioselectivity